Kan omvendt undervisning gi bedre læringsutbytte i legemiddelregning, sammenlignet med tradisjonell undervisning? En kvasieksperimentell kontrollert studie - Tørris, Christine (Nordisk tidsskrift for helseforskning, 2020)
Flipped classroom improves student learning in dosage calculation, - a quasi-experimental control group designThe flipped classroom method has received increased attention in health sciences education, however, few studies have investigated performance data showing its effectiveness. The aim of this study was to compare learning outcome in a flipped classroom with a standard lecture. The hypothesis was that applying a flipped classroom model in a dosage calculation class would improve learning outcome when compared to standard learning. One group was assigned to a flipped classroom (n=43), and the other group to a traditional lecture-based classroom (n=45). Data were collected through answer sheets and test results. Course content, assessments, and instructional time for both models were equivalent. The social educator students in the flipped group performed better in the test, compared to the traditional group, where the flipped group had 22% reduction in failing the exam.The flipped classroom approach is promising as an acceptable approach for teaching in dosage calculation curricular in higher education.
Keywords: flipped classroom; student involvement; student active learning forms; just in time teaching; blended learning; peer instruction; omvendt undervisning; studentinvolvering; studentaktive læringsformer; tilpasset undervisning